'We are being Pilloried for Something, We Did Not Even Know We Had Done Wrong!' Quality Control and Orders of Worth in the British Audit Profession. (27th February 2013) - Ramirez, Carlos
Abstract This paper contributes to the analysis of institutional work by looking at situations of perceived injustice that institutional change can create. To this end, the paper mobilizes the work of Boltanski and Thévenot on orders of worth to analyse the consequences for a professional body of a shift in institutional logics towards more accountability. The feeling of injustice experienced – and voiced – by some members of the largest British institute of auditors, the ICAEW, after it set up and operated a quality monitoring unit, serves to illustrate how change can turn awry when equity in a community of peers is threatened, and how institutional work can remedy such a situation by restoring a sense of worth in the community.